Sistema UPQC multifuncional proposto para operar como interface entre microrredes híbridas e redes concessionárias de energia elétrica - Bacon, Vinicius Dario (2020)
This doctoral thesis presents a multifunctional hybrid unified power quality conditioner (UPQC-H), which is proposed to operate as an interface between utility grids and hybrid microgrids (H-μG). The UPQC-H forms the and buses for H-μG and integrates both the distributed generation systems (DGS) and energy storage systems (ESS). In order to achieve the cited functionalities, the proposed UPQC-H includes two additional power switches to the traditional three-phase UPQC power circuit, which is commonly composed of two three-phase inverters used to operate as series and parallel converters. Some advantages related to the proposed UPQC-H configuration can be highlighted, as follows: 1) versatile application to any H-μG configuration; 2) natural power exchange between the hybrid and buses in both grid-connected and islanded operating modes; 3) seamless transitions between the islanded and grid-connected operating modes, and vice versa. 4) smoothing of the problems associated with the RES intermittencies. Extended experimental and computational results are presented to validate the proposal and explore the multifunctionalities of the UPQC-H interfacing a threephase utility grid and a H-μG, and, simultaneously, integrating photovoltaic-based DGS and ESS based on battery bank.